Comparative Lipidomics and microstructural characterization of Milk fat globule membrane protein powders from bovine buttermilk and cheese whey - Kuolin Si; Mengxueyao Zhang; Xuexing Zong; Yin Pei; Lu Liu; Xiuxiu Zhang; Meiling Ge; Xiaodong Li; Qingquan Yan (Food Research International, 2026)

Regional climate downscaling simulations for China since the Last Glacial Maximum - Naixin Cao; Liang Ning; Jian Liu; Zhengyu Liu; Mi Yan; Weiyi Sun; Meiling Jiang; Xueyuan Kuang; Huayu Lu; Kefan Chen; Yanmin Qin; Qin Wen; et al. (Science China Earth Sciences, 2026)

Spatiotemporal cube for identifying Cd-dominated heavy metal stress in rice using signal decomposition and hotspot analysis from GF-6 time series images - Yanan Wen; Tianyi Wang; Meiling Liu; Hui Zhang; Yuxin Zhao; Ben Yang; Xutao Yan; Ling Wu (International Journal of Remote Sensing, 2026)

Bionic construction and performance assessment of 3D bioprinted small-diameter artificial blood vessels - Yuan-Zhu Xin; Wenyu Jin; Qianqian Wu; JunHee Lee; Geng Li; Yan Chen; Jun Liu; Seok-Jo Yang; Jiazi Gao; Meiling Quan; Zhenning Liu (Chemical Engineering Journal, 2026)

Design and Performance Evaluation of Amino Acid-Decorated UiO-66-NH2/Pebax Mixed Matrix Membranes for Efficient CO2 Separation - Xiaochun Jing; Wei Zhao; Pengzhi Bei; Hongjing Liu; Yan Dai; Xu Zhao; Chengpeng Zhang; Meiling Shi; Ying Zhang (Water, Air, & Soil Pollution, 2026)

Impacts of vegetation management on pollination network structure and robustness in urban parks: A case study from Beijing Wenyu River Park - Yaxuan Li; Meiling Shu; Chenxi Li; Liwen Liu; Yan Zhou; Lan Wu; Yuyu Wang (Urban Ecosystems, 2026)

Spatiotemporal Profiling of Intratumoral Free Payload Distribution via MALDI Imaging Mass Spectrometry: Implications for Drug-to-Antibody Ratio Optimization in Antibody–Drug Conjugates - Tingting Cai; Ziyi Li; Qiaofang Yan; Guangcun Huang; Kaiying Jia; Xiaotong Chen; Junling Dun; Jinghua Zou; Meiling Tan; Yue Wu; Fan Wang (The AAPS Journal, 2026)

Shifting patterns in tropical lake phytoplankton communities coinciding with anthropogenic nutrient and pollutant trends - Dongna Yan; Yongming Han; Patrick Rioual; Jianghu Lan; Sifan Zan; Yalan Tang; Huijia Zhang; Meiling Guo; Eric Capo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Coupled crack-rainfall mechanism of a retrogressive landslide: field investigation and monitoring in Southwest China - Qiuxiang Huang; Shupeng Li; Meiling Xiong; Chu Zhang; Yan Zhou (Bulletin of Engineering Geology and the Environment, 2026)

Stability and Transport of Ferrihydrite Nanoparticles in Alkaline Soils - Yan Gong; Meiling Wang; Shuting Tian; Qingwei Ding; Xia Li; Gaiqiang Yang; Qi Liu; Juanfang Yang; Lijuan Huo (Water, Air, & Soil Pollution, 2026)

Metagenomic and metatranscriptomic characterization of syntrophic propionate- and butyrate-oxidizing bacterial communities in Qiangyong proglacial lake sediments on the Qinghai-Tibet Plateau - Rong Wen; Hongfei Chi; Meiling Feng; Yang Zhao; Chengfang Ma; Keshao Liu; Qi Yan; Pengfei Liu (Soil Ecology Letters, 2026)

Evaluation of the antibacterial and antioxidant potential of the endophytic fungus EFY14 from Cannabis sativa L. leaves through metabolomics and molecular docking - ShanShan Li; MeiLing Zhang; Ying Zhai; Yan Zhao; Ming Zhao; LiJie Liu; FeiYao Zhong; ZhiGang Wang; Shuai Li (Natural Product Research, 2026)

Impact of Drought‐Flood Abrupt Alternation on Vegetation Productivity in Karst and Non‐Karst Regions of Southern China - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (International Journal of Climatology, 2026)
Drought‐flood abrupt alternation (DFAA)—characterised by rapid transitions between drought and flood events—is an extreme compound natural hazard that threatens ecosystems, particularly in fragile environments such as karst regions. Soil moisture is a key indicator of surface hydrological processes, directly regulating vegetation growth and recovery. This study utilises the Standardised Soil Moisture Index (SSMI) to identify DFAA events and applies Granger causality analysis to reveal soil moisture‐vegetation interactions. The impact of DFAA on vegetation productivity is quantified, with a comparative analysis between karst and non‐karst regions in southern China. The results indicate that: (1) From 2000 to 2020, SSMI showed a significant upward trend. Drought‐to‐flood events were more frequent, intense, and longer in duration than flood‐to‐drought events. Both types of events also exhibited substantial spatial heterogeneity. (2) SSMI and NDVI were positively correlated, with the strongest correlation reaching 0.32 at a 60‐day lag. Bidirectional causality between SSMI and NDVI was predominant, affecting 49.24% of the study area. (3) Flood‐to‐drought events synergistically intensified drought–flood stress, whilst drought‐to‐flood events mitigated stress effects. Consequently, vegetation recovery was slower after flood‐to‐drought events, particularly in hydrologically vulnerable karst regions.

Impact of soil moisture depth variation on agricultural drought monitoring in karst and non-karst areas of southwest China: a case study of Yunnan Province - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (CATENA, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Breast Cancer Bone Metastasis: Novel Prognostic Biomarkers Identified - Meiling Chu; Yan Zhang; Jie Chen; Hui Cong; Yulian Yin; Hongfeng Chen (Phenomics, 2025)

CO2 selective adsorption from CO2/CH4 mixtures and regeneration of X zeolites by Li and K modification using various regeneration strategies - Yongbiao Sun; Hui Li; Haijun Lai; Yan Yu; Meiling Hou; Chao Fu; Zaizhou Wang; Chunxiang Zhang (Chemical Engineering Journal, 2025)

Confining PMo12 in flexible nanocages for enhanced electrochemical energy storage - Yuanyuan Yan; Chongji Wang; Yuhang Chen; Cao Wu; Kezhuo Xie; Zhenyu Liu; Tianyuan Zhang; Weifeng Liu; Xuguang Liu; Tian Wang; Zhaofeng Chen; Shengbo Sang; et al. (Chemical Engineering Journal, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

A Hypothetical Protein Fragment from Large Yellow Croaker (Larimichthys crocea) Demonstrates Significant Activity Against Both Bacterial and Parasite - Chunmei Yan; Meiling Chen; Hao Xu; Jian Jin; Xiande Liu; Zhiyong Wang; Dongling Zhang (Fishes, 2025)
Antimicrobial peptides (AMPs) are biocompatible and biodegradable, making them an attractive alternative to traditional antimicrobial agents and chemical preservatives. Here, a novel α-helix amphiphilic anionic AMP Lc149 was screened from a large yellow croaker (Larimichthys crocea) using a Bacillus subtilis expression system. Lc149 is a hypothesized protein fragment not annotated in the genome of a large yellow croaker. Both extracellular protein and recombinant Lc149 (rLc149) exhibited significant killing effects against Gram-negative Escherichia coli and Vibrio harveyi. Scanning and transmission electron microscopy revealed that rLc149 had the ability to disrupt bacterial cell membranes, causing irregular cell morphology, severe cell membrane damage, cytoplasm agglutination, and intracellular content leakage. Confocal laser scanning microscopy and flow cytometry further confirmed bacterial cell destruction and mortality rates of over 80%. Gel retardation assays and SDS-PAGE electrophoresis showed that rLc149 was unable to bind to bacterial DNA, but did reduce bacterial protein contents. Additionally, rLc149 maintained antibacterial activity against E. coli and V. harveyi upon exposure to temperatures of 25–100 °C, UV radiation time of 0–60 min, pH levels of 3–12, and different proteases. Biosafety assays revealed low hemolytic toxicity to erythrocytes of large yellow croaker, rabbit, and shrimp, and low cytotoxicity to large yellow croaker kidney cells and HEK 293T cells. More deeply, rLc149 also possessed significant killing activity against parasites. Therefore, rLc149 can be considered an antibacterial and antiparasitic drug in fisheries.

Methyltransferase HsdM Regulates the Pathogenicity of Streptococcus agalactiae to Nile Tilapia (Oreochromis niloticus) - Dongdong Jiang; Bei Wang; Yan Ren; Xubing Mo; Meiling Yu; Defeng Zhang (Fishes, 2025)
DNA methylation is a critical mechanism for regulating gene expression in bacteria and plays an essential role in bacterial pathogenesis. A mutant, WC1535ΔhsdM, lacking hsdM encoding a DNA methyltransferase was constructed using homologous recombination technology. The growth, hemolytic activity, and capsule formation of the mutant were analyzed. The dynamic distribution of the wild-type (WT) and mutant strains in tilapia tissues after artificial infection was determined. The adhesion, invasion, anti-phagocytic, and whole-blood survival abilities of the WT and mutant strains were analyzed. Tilapia were intraperitoneally injected with the WT or mutant strains, and the LD50 values were determined. The expression levels of the immune-related genes in tilapia were analyzed by qRT-PCR. The mutant showed faster growth during the logarithmic growth period (5–10 h) and lower hemolytic activity than the WT strain. Mutant loads in tilapia tissues were significantly lower than those of the WT strain. Mutant strain adhesion to epithelial cells was significantly reduced, it was more easily engulfed by macrophages, and it had decreased intracellular survival. The LD50 of the mutant was 2.06 times higher than that of the WT strain, indicating decreased pathogenicity. Expression levels of immune-related genes IL-1β, IL-6, IFN-γ, and TNF-α in tilapia induced by the mutant were lower than those by the WT strain. In conclusion, the WC1535ΔhsdM mutant exhibited an increased growth rate and decreased hemolytic activity, tissue colonization, and pathogenicity, indicating that HsdM could regulate S. agalactiae growth and pathogenicity. This study provides new insights into the pathogenesis of piscine S. agalactiae.

Highly selective capture of Ni2+ from complex environments by a sandwich-like layered metal sulfide ion exchanger - Mingdong Zhang; Qisheng Hong; Yuan Aocheng; Yan Zhang; Xiaoying Huang; Meiling Feng; Jingli Mu (Journal of Hazardous Materials, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Bacillus subtilis 2118 exhibits bactericidal activity due to an inserted fish cDNA library - Chunmei Yan; Meiling Chen; Jian Jin; Xiande Liu; Zhiyong Wang; Yongju Luo; Dongling Zhang (Aquaculture, 2024)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

MicroRNA expression profiles in plasma exosomes of late pregnant giant pandas - Meiling Cheng; Yingmin Zhou; Qian Wang; Bo Luo; Yanwu Lai; Jianbin Cheng; Xiuyue Zhang; Yan Huang; Desheng Li (Molecular Biology Reports, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

A novel and convenient lying cow identification method based on YOLOX and CowbodyNet: A study with applications in a barn - Jianxing Xiao; Yongsheng Si; Meiling Xie; Gang Liu; Zhang Yan; Kejian Wang (Computers and Electronics in Agriculture, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Nanoarchitectonics of bamboo-based heterojunction photocatalyst for effective removal of organic pollutants - Xiaole Yan; Meiling Chen; Junning Wang; Zhaodong Wang; Ruiqi Xin; Dujuan Wu; Ye Song; Song Li; Wenkai Zhu; Chaohai Wang; Yanli Mao (Chemical Engineering Journal, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

STAT2 negatively regulates RIG-I in the antiviral innate immunity of black carp - Ji Liu; Chushan Dai; Lijun Yin; Xiao Yang; Jun Yan; Meiling Liu; Hui Wu; Jun Xiao; Weiguang Kong; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Green and efficient approach to extract bioactive flavonoids with antioxidant, antibacterial, antiglycation, and enzyme inhibitory activities from navel orange peel - Chunling Lai; Meiling Huang; Qin Xiong; Yan Liang; Yueming Jiang; Jun Zhang (Sustainable Chemistry and Pharmacy, 2024)

A prototype galectin-1 (also known as galecin-2) from large yellow croaker (Larimichthys crocea): Molecular and function study - Xin Tang; Zhiqun Xiao; Meiling Chen; Jian Jin; Chunmei Yan; Xingcheng Zhu; Zhiyong Wang; Dongling Zhang (Fish & Shellfish Immunology, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Designing a cercosporin-bioinspired bifunctional algicide with flocculation and photocatalysis for efficiently controlling harmful cyanobacterial blooms - Zhenbo Yuan; Meiling Liu; Zengping Su; Huibin Xu; Changmei Liu; Liushen Lu; Lingling Wang; Xiaonan Zhu; Yan Zhang; Yijian Rao (Journal of Hazardous Materials, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

A Quad-Functional On-demand released nanomissile achieves cascade amplification therapy of Triple-Negative breast cancer through reversing multiple resistance - Yan Wang; Xianzhou Huang; Shunyao Zhu; Lu Li; Jin Yang; Jie Li; Li Wang; Shuang Ma; Meiling Shen; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Tet Enzyme-Mediated Response in Environmental Stress and Stress-Related Psychiatric Diseases - Meiling Xia; Rui Yan; Myoung-Hwan Kim; Xingshun Xu (Molecular Neurobiology, 2023)

SnoRNP is essential for thermospermine-mediated development in Arabidopsis thaliana - Xilong Li; Zongyun Yan; Meiling Zhang; Jiayin Wang; Peiyong Xin; Shujing Cheng; Liquan Kou; Xiaoting Zhang; Songlin Wu; Jinfang Chu; Chengqi Yi; Keqiong Ye; et al. (Science China Life Sciences, 2023)

Integrated eco-physiological, biochemical, and molecular biological analyses of selenium fortification mechanism in alfalfa - Qingdong Wang; Jinke Hu; Huafeng Hu; Yan Li; Meiling Xiang; Dezhen Wang (Planta, 2022)

Morphological and endogenous phytohormone changes during long-term embryogenic cultures in Korean pine - Yan Liang; Xin Xu; Hailong Shen; Meiling Gao; Yan Zhao; Xue Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Brain Dicer1 Is Down-Regulated in a Mouse Model of Alzheimer’s Disease Via Aβ42-Induced Repression of Nuclear Factor Erythroid 2-Related Factor 2 - Yan Wang; Meiling Lian; Jing Zhou; Shengzhou Wu (Molecular Neurobiology, 2020)

Malus niedzwetzkyana (Dieck) Langenf transcriptome comparison and phylogenetic analysis with Malus sieversii (Ledeb) Roem - Meiling Yang; Shiyou Che; Yunxiu Zhang; Wenqin Song; Guorong Yan; Weiwei Yu (Genetic Resources and Crop Evolution, 2020)

Two new monoterpene glucosides from Xanthium strumarium subsp. sibiricum with their anti-inflammatory activity - Hai Jiang; Xudong Xing; Meiling Yan; Xinyue Guo; Lin Yang; Liu Yang (Natural Product Research, 2019)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Genome-wide investigation of microsatellite polymorphism in coding region of the giant panda (Ailuropoda melanoleuca) genome: a resource for study of phenotype diversity and abnormal traits - Meiling Cheng; Jianying Ren; Fujun Shen; Yan Huang; Zhenxin Fan; Megan Price; Bisong Yue; Xiuyue Zhang (Mammal Research, 2019)

Genome-wide identification of the pectate lyase-like (PLL) gene family and functional analysis of two PLL genes in rice - Yinzhen Zheng; Junjie Yan; Shuzhen Wang; Meiling Xu; Keke Huang; Guanglong Chen; Yi Ding (Molecular Genetics and Genomics, 2018)

Development of Fluorescence-Linked Immunosorbent Assay for Icariin - Jinjun Cheng; Yan Zhao; Meiling Zhang; Yue Zhang; Xiaoman Liu; Xin Yan; Yongzhi Wang; Ziwei Sun; Qingguo Wang; Huihua Qu (Journal of Fluorescence, 2017)

Genome-wide survey and expression analysis of the calcium-dependent protein kinase gene family in cassava - Wei Hu; Xiaowan Hou; Zhiqiang Xia; Yan Yan; Yunxie Wei; Lianzhe Wang; Meiling Zou; Cheng Lu; Wenquan Wang; Ming Peng (Molecular Genetics and Genomics, 2016)

Long-term cultured callus and the effect factor of high-frequency plantlet regeneration and somatic embryogenesis maintenance in Zoysia japonica - Li Liu; Xiaoli Fan; Junwei Zhang; Meiling Yan; Manzhu Bao (In Vitro Cellular & Developmental Biology - Plant, 2009)